2010
DOI: 10.2217/whe.10.34
|View full text |Cite
|
Sign up to set email alerts
|

Fallopian Tube Recanalization: Lessons Learnt and Future Challenges

Abstract: Technological advances in fiberoptics and endoscopy have resulted in the development of minimally invasive transcervical tubal catheterization procedures with the potential of improved diagnostic accuracy of tubal disease and transcervical treatment of proximal tubal obstruction (PTO) with reduced risks, costs and morbidity compared with surgical procedures. Fallopian tube recanalization can be performed with catheters, flexible atraumatic guidewires or balloon systems under endoscopic (falloposcopy/hysterosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 68 publications
(119 reference statements)
0
21
0
3
Order By: Relevance
“…Intraluminal pathology of the fallopian tube (IPFT) is correlated with two conditions-pelvic inXammatory disease and endometritis [1]. The presence of such tubal disease is a strong determinant of infertility [2]; 20-25% of infertile women have been shown to have endometriosis compared with 2-5% of fertile women [3], and up to a third of women with endometriosis show evidence of salpingitis [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraluminal pathology of the fallopian tube (IPFT) is correlated with two conditions-pelvic inXammatory disease and endometritis [1]. The presence of such tubal disease is a strong determinant of infertility [2]; 20-25% of infertile women have been shown to have endometriosis compared with 2-5% of fertile women [3], and up to a third of women with endometriosis show evidence of salpingitis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Two kinds of endometritis are discerned: acute endometritis characterized by an edema of bleeding endometrium, covered by an abnormal mucus; chronic endometritis with areas of red endometrium, Xushed, with a white central point, localized or scattered out the cavity. This is the "strawberry aspect" [1]. Whereas severe cases of endometritis accompanied by extensive pelvic adhesions can lead to tubal infertility, mild or moderate cases with no tubal damage are also associated with infertility, suggesting an immunological rather than a mechanical barrier to reproduction [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…One study that was reviewed reported a success rate of 13.3% for distal tubal occlusion after hysteroscopic tubal cannulation. 9 …”
Section: Tubal Cannulation and Artmentioning
confidence: 99%
“…It can be performed with catheters, guidewires or balloon systems under sonographic, fluoroscopic or hysteroscopic guidance [28]. Houston and Machan [29] evaluated the technical success and outcome of FTR in SIN.…”
Section: Interventional Radiologymentioning
confidence: 99%